Clinical impact of low-volume lymph node metastases in early-stage cervical cancer: A comprehensive meta-analysis - Guani, Benedetta; Mahiou, Katia; Crestani, Adrien; Cibula, David; Buda, Alessandro; Gaillard, Thomas; Mathevet, Patrice; Kocian, Roman; Sniadecki, Marcin; Wydra, Dariusz G; Feki, Anis; Paoletti, Xavier; et al. (Gynecologic oncology, 2022)
OBJECTIVE: In order to define the clinical significance of low-volume metastasis, a comprehensive meta-analysis of published data and individual data obtained from articles mentioning micrometastases (MIC) and isolated tumor cells (ITC) in cervical cancer was performed, with a follow up of at least 3 years. METHODS: We performed a systematic literature review and meta-analysis, following Cochrane's review methods guide and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The primary outcome was the disease-free survival (DFS), and the secondary outcome was the overall survival (OS). The hazard ratio (HR) was taken as the measure of the association between the low-volume metastases (MIC+ITC and MIC alone) and DFS or OS; it quantified the hazard of an event in the MIC (+/- ITC) group compared to the hazard in node-negative (N0) patients. A random-effect meta-analysis model using the inverse variance method was selected for pooling. Forest plots were used to display the HRs and risk differences within individual trials and overall. RESULTS: Eleven articles were finally retained for the meta-analysis. In the analysis of DFS in patients with low-volume metastasis (MIC + ITC), the HR was increased to 2.60 (1.55-4.34) in the case of low-volume metastasis vs. N0. The presence of MICs had a negative prognostic impact, with an HR of 4.10 (2.71-6.20) compared to N0. Moreover, this impact was worse than that of MIC pooled with ITCs. Concerning OS, the meta-analysis shows an HR of 5.65 (2.81-11.39) in the case of low-volume metastases vs. N0. The presence of MICs alone had a negative effect, with an HR of 6.94 (2.56-18.81). CONCLUSIONS: In conclusion, the presence of MIC seems to be associated with a negative impact on both the DFS and OS and should be treated as MAC.
Keywords: Ultrastaging; sentinelová uzlina; Low-volume lymph node metastasis; spinocelulární karcinom; Cervical cancer; Sentinel Lymph Node Biopsy; Sentinel lymph node; mikrometastázy; lymfatické metastázy; adenokarcinom; Lymph Nodes; míra přežití; nádory děložního čípku; Neoplasm Micrometastasis; Lymphatic Metastasis; Neoplasm Staging; Disease-Free Survival; ženské pohlaví; Humans; Tumor Burden; tumor burden; Survival Rate; Sentinel Lymph Node; lymfatické uzliny; staging nádorů; Uterine Cervical Neoplasms; Carcinoma, Squamous Cell; biopsie sentinelové lymfatické uzliny; Female; Adenocarcinoma; přežití bez známek nemoci; lidé